Polemiche letterarie e nazionalistiche. A proposito del “ritrovamento” del ms. Vat. Lat. 3195 - PULSONI, Carlo (Giornale Italiano di Filologia, 2021)
Abstract L’articolo ricostruisce le polemiche successive alla riscoperta nel 1886 del manoscritto originale del Canzoniere di Francesco Petrarca, ms. Vaticano latino 3195, nella Biblioteca Apostolica Vaticana. La vicenda non si limita alla questione filologica ma investe anche l’aspetto nazionalistico, a causa della recente presa di Roma. Abstract [Literary and Nationalistic Disputes. About the “Rediscovery” of ms. Vat. lat. 3195] The article reconstructs the controversies following the rediscovery in 1886 of the original manuscript of Petrarch’s Canzoniere, ms. Vatican Latin 3195, in the Vatican Apostolic Library. The matter is not limited to the philological question but also affects the nationalistic aspect, due to the recent taking of Rome by united Italy.